Percutaneous closure of the patent foramen ovale: A cardiological perspective - Brown, S.C. (SA Heart Journal, 2017)
A patent foramen is commonly found in the general population.Evidence exists that a patent foramen ovale (PFO) and atrial septal aneurysm are strongly associated with cryptogenic stroke. Associations with migraine have also been described, but the status of cause and effect is less clear. Management of PFO is controversial and no form of therapy has been properly evaluated. PFO closure devices are readily available and can be safely and effectively implanted percutaneously. Complication rates are low and symptoms are improved in most patients. At present, there is a lack of guidelines for the treatment of PFO and results of prospective randomised trials are eagerly awaited.